2020
DOI: 10.1177/0042098020910698
|View full text |Cite
|
Sign up to set email alerts
|

Do rising rents lead to longer commutes? A gravity model of commuting flows in Ireland

Abstract: The classical monocentric city model suggests that property prices decrease and transport costs rise with distance to the urban centre, implying that employees face a trade-off between long commutes and high housing costs when making location decisions. Accordingly, some commuters might be forced to take on longer commutes due to rising rents in central locations. In this study, we investigate empirically whether the rental differential between employment centres and residential areas predicts changes in avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Liu concluded that accounting for spatial and temporal dependence is not only theoretically warranted, but contributes to better prediction performance. Ahrens and Lyons (2021) construct a model linking commuting times to rental prices in the Dublin region, with rising rents linked to shorter commuting times showing the importance of spatial proximity in valuation models. Lyons (2019) explores the relationship between the advertised asking price for dwellings that are listed on estate agent platforms and final sale prices, showing they act as a good proxy.…”
Section: Geo-spatial Modellingmentioning
confidence: 99%
“…Liu concluded that accounting for spatial and temporal dependence is not only theoretically warranted, but contributes to better prediction performance. Ahrens and Lyons (2021) construct a model linking commuting times to rental prices in the Dublin region, with rising rents linked to shorter commuting times showing the importance of spatial proximity in valuation models. Lyons (2019) explores the relationship between the advertised asking price for dwellings that are listed on estate agent platforms and final sale prices, showing they act as a good proxy.…”
Section: Geo-spatial Modellingmentioning
confidence: 99%
“…Within nations, the concentration of land in the hands of a few generates and perpetuates unequal and unsustainable national transformation. Rental increases drive sprawl and longer commuting patterns (Ahrens & Lyons, 2020). Land concentration also explains widespread insecurities which, in turn, drive the rise of gated housing estates (Ehwi et al, 2019).…”
Section: Limits To Inequalitymentioning
confidence: 99%
“…With an increase in urbanization and an imbalance of supply and demand for accommodations in many areas, finding affordable housing is challenging [1,2]. Often, the associated housing scarcity is caused by geographical or regulatory constraints [3,4], forcing tenants to accept high rent prices or long commute times [5,6]. However, long commutes can lead to several impairments, including increasing traffic volume and greenhouse emissions.…”
Section: Introductionmentioning
confidence: 99%